우리나라 중학교 청소년의 우울과 관련요인 - 박형수; 노지숙; 배상열; 최문실; 고대식; 박종; Park, Hyung-Su; Noh, Ji-Sook; Bae, Sang-Yeol; Choi, Moon-Sil; Ko, Dae-Sik; Park, Jong (韓國學校保健學會誌, 2010)
Purpose: This study was aimed to identify factors related with depression among boys and girls in Korean middle school adolescents. Methods: This study used the data from the 2007 annual survey of youth health behaviors conducted by the Korea Centers for Disease Control and Prevention between the period of 2007/9/1 and 2007/9/22 (with the extension of 2007/10/1 and 2007/11/3). The target number of this study was 21,047 male and 18,424 female students all in the age group of middle school 1st grade and 3rd grade. Results: Depression of middle school adolescents was 33.4% for male students, 43.8% for female students, 38.3% in overall. With regard to the relationship between the demographic characteristics and the health behavior, both male and female students felt more depressed when they had more stress, followed by the cases with stimulant intakes and chronic diseases. For male students, higher level of physical activity was associated with greater level of the depression. For female students, living with only one parent or other person seem to cause more depression. Conclusion: Depression of middle school adolescents requires a special attention from the family, the school and society in general to find out and eliminate the root of these symptoms.